Pengaruh Sistem Pengendalian Internal Dan Kompetensi Sumber Daya Manusia Terhadap Akuntabilitas Kinerja Instansi Pemerintah (Studi Kasus Pada Instansi Pemerintah Daerah Kota Cimahi) - Annisa Putri Kharisma; Hani Fitria Rahma (Jurnal Akuntansi dan Keuangan Daerah, 2023)
The results of the performance accountability evaluation of Cimahi City government agencies from 2015 to 2018 scored C and B. This shows that performance accountability in the Cimahi City Government still has some deficiencies that must be corrected because SAKIP and LAKIP need to be supported by competent human resources and have elements monitoring. This study aims to find out the effect of the Internal Control System and Human Resource Competence on the Performance Accountability of Government Agencies. The population in this study were BKPSDMD employees and the Inspectorate of Cimahi City, with 71 respondents. The sampling technique uses the census method. The data was processed using SPSS version 26 software with multiple linear regression analysis techniques. The results of this study prove that the Internal Control System and Competence of Human Resources partially and simultaneously influence the Performance Accountability of Government Agencies.